FULFILLMENT OF THE RIGHTS OF CHILDREN IN CONFLICT WITH THE LAW IN THE WOMEN AND CHILDREN SERVICE UNIT OF THE ROKAN HULU RESORT POLICE BASED ON LAW NUMBER 11 OF 2012 CONCERNING THE JUVENILE CRIMINAL JUSTICE SYSTEM - Hutabarat, santa Delima; Fahmi, Fahmi; Pardede, Rudi (EKSEKUSI, 2024)
ABSTRACTArticle 33 paragraph (5) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, states that: "In the event that there is no Temporary Child Placement Institution, detention can be carried out at the local Social Welfare Organizing Institution." The aim of the research is to analyze the arrangements for fulfilling children's rights at the Rokan Hulu Resort Police based on these regulations; To analyze the fulfillment of children's rights at the Rokan Hulu Resort Police based on these regulations. The research method is sociological legal research, statutory and case approaches; the research location is the Rokan Hulu Resort Police; population and samples of relevant sources; data sources are primary, secondary and tertiary; Data collection techniques are observation, structured interviews and document/library study; Data analysis is qualitative with inductive conclusion drawing.  The results of the research are that these regulations have not been implemented in the Women and Children Protection Unit of the Rokan Hulu Resort Police for children in conflict with the law. The results of the research are, First, the arrangements for fulfilling children's rights in the Women's and Children's Services Unit of the Rokan Hulu Resort Police are based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, with jurisdiction the provisions in Article 33 paragraph (5) of the regulation apply. Second, the fulfillment of the children's rights in the Unit based on these regulations was not implemented, they were instead left in the detention cells of the Rambah Sector Police and mixed in one cell with adult prisoners. This is due to several factors, namely legal/legislative factors, non-regulation of sanctions, namely inadequate legal products to overcome the problem of the absence of LPSK buildings; There are no regional regulations that further regulate the obligations for the development/provision of LPSK. The law enforcement/government apparatus factor, namely the local regional government, in the APBD it prepares, never budgets for the establishment and implementation of LPSK in Rokan Hulu Regency. Facilities/facilities factor, namely people who do not understand the law and therefore do not know that children detained in the investigation process at the police level have the right to be detained at the LPSK. Community factors; namely LPSK does not exist in Rokan Hulu Regency; For the purposes of investigations at the police level it can only be carried out within a maximum of 7 (seven) days so that it is not time and cost efficient if carried out.Keywords: LPSK, Children, Rokan Hulu ABSTRAKPasal 33 ayat (5) Undang–Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak, bahwa: Dalam hal tidak terdapat Lembaga Penempatan Anak Sementara, penahanan dapat dilakukan di Lembaga Penyelenggaraan Kesejahteraan Sosial setempat.” Tujuan penelitian ialah Untuk menganalisis pengaturan pemenuhan hak Anak tersbeut di Kepolisian Resor Rokan Hulu berdasarkan regulasi tersebut; Untuk menganalisis pemenuhan hak Anak tersebut di Kepolisian Resor Rokan Hulu berdasarkan regulasi tersebut. Metode penelitiaan ialah penelitian hukum sosiologis, pendekatan perundang–undangan dan kasus; lokasi penelitian yaitu Kepolisian Resor Rokan Hulu; populasi dan sampel dari narasumber–narasumber yang relevan; sumber data ialah primer, sekunder dan tersier; teknik pengumpulan data ialah observasi, wawancara terstruktur dan studi dokumen/kepustakaan; analisis data ialah kualitatif dengan penarikan  kesimpulan induktif.  Hasil penelitian yaitu regulasi tersebut belum terlaksana di Unit Perlindungan Perempuan dan Anak Kepolisian Resor Rokan Hulu terhadap anak yang berkonflik dengan hukum. Hasil penelitian ialah, Pertama, Pengaturan pemenuhan hak Anak  tersebut di Unit Pelayanan Perempuan dan Anak Kepolisian Resor Rokan Hulu berdasarkan Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak secara yurisdiksi berlaku ketentuan dalam Pasal 33 ayat (5) regulasi tersebut. Kedua, Pemenuhan hak Anak tersebut di Unit itu berdasarkan regulasi tersebut tidak terlaksana, mereka justru di titipkan di sel tahanan Kepolisian Sektor Rambah dan berbaur satu sel dengan tahanan dewasa. Hal tersebut disebabkan beberapa faktor, yaitu Faktor hukum/peraturan perundang-undangan, tidak diaturnya sanksi yaitu Produk hukum yang tidak memadai untuk mengatasi permasalahan tidak adanya bangunan LPSK; Tidak adanya peraturan daerah k yang mengatur lebih lanjut mengenai kewajiban pembangunan/ penyediaan LPSK. Faktor aparat penegak hukum/pemerintah yaitu Pemerintah daerah  setempat dalam APBD yang disusunnya tidak pernah menganggarkan pendirian dan penyelenggaraan LPSK di Kabupaten Rokan Hulu. Faktor sarana/fasilitas, yaitu masyarakat yang tidak paham hukum sehinga tidak mengetahui bahwa anak yang ditahan dalam proses penyidikan di tingkat kepolisian mendapatkan hak penahanan di LPSK. Faktor masyarakat; yaitu LPSK tidak ada di Kabupaten Rokan Hulu; untuk kepentingan penyidikan di tingkat kepolisian hanya boleh dilakukan paling lama 7 (tujuh) hari sehingga tidak efisiensi waktu dan biaya jika dilakukan.Kata Kunci: LPSK, Anak, Rokan Hulu